PhD Programs as a Basic Tool of Human Capacity Building in Russian Science - E. V. Karavaeva; O. A. Kostenko; V. V. Malandin; I. A. Mosicheva (Высшее образование в России)
The article addresses the problem of staffing of the Russian science and examines the issues pertaining to the training of research and pedagogical personnel at the PhD-programs in the light of forthcoming transition to a new model of doctoral studies (Federal Law №517-FZ of December 30, 2020). The authors assert that one of the reasons for a decrease in the number of professionals (particularly young ones) engaged in research and development in the Russian Federation is the underestimation of the role of PhD-programs in the continuous replenishment of human resources. The article assesses recent regulations and requirements containing approaches to the organization of research and pedagogical personnel training on doctoral programs that will be effective from March 2022, discusses the prospects for the doctoral education and the risks involved.